Serum-Induced Expression of the cdc25A Gene by Relief of E2F-Mediated Repression - Chen, Xi (American Society for Microbiology, 1999)
The cdc25A gene encodes a tyrosine phosphatase which activates cyclin-dependent kinase activity in the G(1) phase of the cell cycle. cdc25A RNA levels are induced from 3 to 6 h after serum induction of serum-starved NIH 3T3 cells, suggesting that the cdc25A gene is a delayed-early gene. Analysis of cdc25A promoter constructs showed that the cdc25A promoter is sufficient for serum induction. Surprisingly for a gene expressed in early to mid-G(1), serum induction of the promoter requires an E2F site at position −62 in the promoter. Deletion or point mutation of the E2F site resulted in activation of expression in serum-starved cells and no further induction by serum treatment. E2F factors were found to bind to the cdc25A E2F site along with the retinoblastoma protein (Rb) family members p130 and p107. A shift in mobility of the E2F-p107 complex in extracts of cells induced for 6 h correlated with induction of cdc25A expression. These results suggest that serum induction of cdc25A expression is mediated by inactivation of p107 or p130, both of which repress transcription when bound to the promoter through E2F.